2022
DOI: 10.3389/fendo.2022.905266
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inflammation and Insulin Resistance Related Indicator to Predict the Survival of Patients With Cancer

Abstract: BackgroundSystemic inflammation and insulin resistance (IR) are closely related in patients with cancer. However, there is no relevant indicator that combines inflammation and IR to predict patient prognosis. Therefore, this study aimed to develop and validate a novel inflammation- and IR-related marker in patients with cancer.MethodsThe total cohort of this study included 5221 patients with cancer, and the training and validation cohorts were randomized in a 7:3 ratio. C-reactive protein (CRP) and fasting tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A recent study pointed out that inflammation assessed by hsCRP was a stronger predictor for risk of future CVD events and death than cholesterol, suggesting that inflammation and hyperlipidemia jointly contribute to atherothrombotic disease and the combined use of aggressive lipid-lowering and inflammation-inhibiting therapies to further reduce atherosclerotic risk [ 20 ]. Moreover, hsCRP and the TyG index have been used to develop the CRP-TyG index (CTI), synchronously reflecting the inflammation and insulin resistance status given the close correlation between inflammation and insulin resistance [ 58 ]. There is also accumulating evidence indicating that chronic inflammation as measured by hsCRP is associated with insulin resistance and other features of insulin resistance syndrome and then leads to increased cardiovascular risk [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study pointed out that inflammation assessed by hsCRP was a stronger predictor for risk of future CVD events and death than cholesterol, suggesting that inflammation and hyperlipidemia jointly contribute to atherothrombotic disease and the combined use of aggressive lipid-lowering and inflammation-inhibiting therapies to further reduce atherosclerotic risk [ 20 ]. Moreover, hsCRP and the TyG index have been used to develop the CRP-TyG index (CTI), synchronously reflecting the inflammation and insulin resistance status given the close correlation between inflammation and insulin resistance [ 58 ]. There is also accumulating evidence indicating that chronic inflammation as measured by hsCRP is associated with insulin resistance and other features of insulin resistance syndrome and then leads to increased cardiovascular risk [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…GCR was statistically significant when compared with the patient and healthy control group ( p < 0.001). In the study conducted by Ruan et al, high values in c-reactive protein triglyceride glucose index (CTI) were found to be associated with poor prognosis in various cancer groups and at different stages [ 41 ]. Since this index includes relatively more complex parameters and is not routinely analyzed in cancer patients, it may not be possible to evaluate it for every patient.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that inflammatory reactions can lead to the occurrence of type 2 diabetes mellitus by participating in IR and further aggravating it in the presence of hyperglycemia, thus promoting multiple long-term diabetes complications [ 22 ]. The TyG index is also considered a reliable marker of systemic inflammation, which can be an inflammatory factor in the progression of DKD [ 23 ]. The multivariable analysis adjusts for potential confounding factors and establishes the fitting equation, while the ROC curve clarifies the sensitivity and specificity of the model, indicating that a high TyG index plays an important role in the pathogenesis of DKD.…”
Section: Discussionmentioning
confidence: 99%